English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

v/(1-v)?

2007-06-11 08:51:28 · 3 answers · asked by joefarmer 1 in Science & Mathematics Mathematics

3 answers

Here is my little trick again.

Write v/(1-v) = (v-1+1)/(1-v) = (v-1)/(1-v) + 1/(1-v)
= -1 + 1/(1-v)

Integrate that to get
v - ln(1-v) + constant

2007-06-11 09:04:20 · answer #1 · answered by Dr D 7 · 1 0

Here it goes:

v/(1-v)

Let u=1-v, then v=1-u, du=-dv

Then,

(u-1) du

=((u^2)/2) - (u) +c

=(((1-v)^2)/2) - (1-v) +c

which is the required answer!!!

2007-06-11 16:02:55 · answer #2 · answered by Abhishek 3 · 0 1

-v - ln(1-v) +C

Doug

2007-06-11 15:59:22 · answer #3 · answered by doug_donaghue 7 · 0 0

fedest.com, questions and answers